An Addressing System on Tetum Language - Antonio Constantino Soares (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study explores the addressing system in Tetum Dili, a prominent variety of the Tetum language spoken in Timor-Leste. Grounded in sociolinguistic and cultural-linguistic frameworks, the research investigates how forms of address reflect social relationships, cultural norms, and communicative values within Timorese society. Utilizing a qualitative descriptive approach, data were collected through semi-structured interviews with native speakers, autoethnographic reflection, and analysis of naturally occurring speech in public events such as wedding ceremonies. The findings reveal that Tetum Dili employs a rich repertoire of address terms, including those based on kinship, honorifics, borrowed forms from Portuguese and Indonesian, and even culturally embedded disrespectful terms used in both friendly and conflictual contexts. These address forms serve as powerful markers of social status, intimacy, respect, and cultural identity. The study underscores the importance of address systems in understanding language use in multicultural and postcolonial contexts, and it advocates for further documentation to support language preservation and education